Labeling Human Melanoma Cells With SPIO - Daniel Spira MD; Rüdiger Bantleon PhD; Hartwig Wolburg PhD; Fritz Schick MD, PhD; Gerd Groezinger MD; Jakub Wiskirchen MD; Benjamin Wiesinger MD (Molecular Imaging)
Objectives: To use the superparamagnetic iron oxide (SPIO) contrast agent Resovist (±transfection agent) to label human melanoma cells and determine its effects on cellular viability, microstructure, iron quantity, and magnetic resonance imaging (MRI) detectability. Materials and Methods: Human SK-Mel28 melanoma cells were incubated with Resovist (±liposomal transfection agent DOSPER). The cellular iron content was measured, and labeled cells were examined at 1.5 T and 3.0 T. The intracellular and extracellular distributions of the contrast agent were assessed by light and electron microscopy. Results: The incubation of melanoma cells with SPIO does not interfere with cell viability or proliferation. The iron is located both intracellularly and extracellularly as iron clusters associated with the exterior of the cell membrane. Despite thorough washing, the extracellular SPIO remained associated with the cell membrane. The liposomal transfection agent does not change the maximum achievable cellular iron content but promotes a faster iron uptake. The MRI detectability persists for at least 7 days. Conclusion: The transfection agent DOSPER facilitates the efficient labeling of human metastatic melanoma cells with Resovist. Our findings raise the possibility that other Resovist-labeled cells may collect associated extracellular nanoparticles. The SPIO may be available to other iron-handling cells and not completely compartmentalized during the labeling procedure.